Sitravatinib as a potent FLT3 inhibitor can overcome gilteritinib resistance in acute myeloid leukemia - Yvyin Zhang; Peihong Wang; Yang Wang; Yang Shen (BMC, 2023)
Abstract Background Gilteritinib is the only drug approved as monotherapy for acute myeloid leukemia (AML) patients harboring FMS-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) mutation throughout the world. However, drug resistance inevitably develops in clinical. Sitravatinib is a multi-kinase inhibitor under evaluation in clinical trials of various solid tumors. In this study, we explored the antitumor activity of sitravatinib against FLT3-ITD and clinically-relevant drug resistance in FLT3 mutant AML. Methods Growth inhibitory assays were performed in AML cell lines and BaF3 cells expressing various FLT3 mutants to evaluate the antitumor activity of sitravatinib in vitro. Immunoblotting was used to examine the activity of FLT3 and its downstream pathways. Molecular docking was performed to predict the binding sites of FLT3 to sitravatinib. The survival benefit of sitravatinib in vivo was assessed in MOLM13 xenograft mouse models and mouse models of transformed BaF3 cells harboring different FLT3 mutants. Primary patient samples and a patient-derived xenograft (PDX) model were also used to determine the efficacy of sitravatinib. Results Sitravatinib inhibited cell proliferation, induced cell cycle arrest and apoptosis in FLT3-ITD AML cell lines. In vivo studies showed that sitravatinib exhibited a better therapeutic effect than gilteritinib in MOLM13 xenograft model and BaF3-FLT3-ITD model. Unlike gilteritinib, the predicted binding sites of sitravatinib to FLT3 did not include F691 residue. Sitravatinib displayed a potent inhibitory effect on FLT3-ITD-F691L mutation which conferred resistance to gilteritinib and all other FLT3 inhibitors available, both in vitro and in vivo. Compared with gilteritinib, sitravatinib retained effective activity against FLT3 mutation in the presence of cytokines through the more potent and steady inhibition of p-ERK and p-AKT. Furthermore, patient blasts harboring FLT3-ITD were more sensitive to sitravatinib than to gilteritinib in vitro and in the PDX model. Conclusions Our study reveals the potential therapeutic role of sitravatinib in FLT3 mutant AML and provides an alternative inhibitor for the treatment of AML patients who are resistant to current FLT3 inhibitors.